IMPLEMENTASI MAQASHID AL-SYARIAH DALAM PENETAPAN UPAH MINIMUM PEKERJA BERBASIS KEADILAN - ZULAIKAH, ZULAIKAH (Universitas Muhammadiyah Surabaya, 2022)
This research is intended to provide a solution in determining the minimum wage for workers that realizes a sense of justice based on values derived from Islamic sharia, so this research is focused on discussing how maqashid al-syariah is used as the basis for determining the minimum wage for workers in order to achieve a sense of justice for both workers and for employers. This research is limited to the following problem formulations: (1) How is the determination of the minimum wage for workers according to positive law; (2) How is the minimum wage for workers determined according to Islamic law; d (3) How is the implementation of maqashid al-syariah regarding the determination of the minimum wage for workers based on justice. This research is normative legal research or library research. The approach used is the statutory approach (that is, an approach in research that uses the law as the basis for its analysis) and the conceptual approach (this approach is used to build a concept where not or have not found clear legal rules regarding the problem under study). The results of this study are: (1) Determination of the minimum wage for workers by the Governor is based on a proposal from the Wage Council. The amount of wages that is considered for its determination is based on the results of a survey conducted by the Wage Council. (2) In Islamic law, the minimum wage is not determined with certainty either by the arguments of the Qur'an or Sunnah, but through the prevailing customs in society with the principle that the minimum wage provided by the employer must be able to meet the basic needs of the worker. and his family. (3) The implementation of maqashid al-syariah regarding the determination of the minimum wage for workers can be realized in the form of implementing sharia commands and abandoning sharia prohibitions in muamalah.Keywords: Maqashid al-Syariah, Minimum Wage, Workers, Justice.